The effect of natural habituation on coagulation responses to acute mental stress and recovery in men - von Känel, Roland; Preckel, Daniel; Zgraggen, Lilian; Mischler, Katharina; Kudielka, Brigitte M.; Haeberli, André; Fischer, Joachim E. (Thrombosis and Haemostasis, 2004)
Blood coagulation activation might be one mechanism linking acute mental stress with coronary events. We investigated the natural habituation of coagulation responses and recovery to short-term mental stress.Three times with one-week intervals, 24 men (mean age 47 ± 7 years) underwent the same 13-min stressor (preparation, job interview, mental arithmetic). During each visit venous blood was obtained four times (baseline, immediately post-stress, 45 min of recovery, 105 min of recovery). Eight blood coagulation parameters were measured at weeks one and three. Acute stress provoked increases in von Willebrand factor antigen, fibrinogen, clotting factor FVII activity (FVII:C), FVIII:C, FXII:C (p’s ≤0.019), and D-dimer (N.S.). All coagulation parameters experienced full recovery except FVIII:C (p = 0.022). Stress did not significantly affect activated partial thromboplastin time and prothrombin time. At all time points FVIII:C and FXII:C levels were significantly higher at week one compared to week three (p’s ≤0.041). Before catheter insertion, systolic blood pressure (p = 0.001) and heart rate (p = 0.026) were relatively higher at week one. Unlike the magnitude of systolic blood pressure response to stress (p = 0.007) and of cortisol recovery from stress (p = 0.002), the magnitude of all coagulation responses to stress and the recovery from stress were similar in week one and week three. Sympathetic activation with anticipatory stress best explained increased baseline activity in FVIII and FXII at week one. An incapacity of the coagulation system to adapt to stress repeats is perhaps a consequence of evolution, but might also contribute to increased coronary risk in some individuals, particularly in those with cardiovascular diseases.
Keywords: Blood coagulation; cardiovascular disease; psychological stress; recovery; habituation